Digital Learning: Differentiated Teaching Models using ICTs In Greek Context - Good Practices: "How Do I Wash My Hands" - Paraskevi, Lykou; Chaidi, Irene; Stathopoulou, Agathi; Karabatzaki, Zoe (Eximia, 2022)
One of the key elements of a person’s growth is their social skills, and motivation is a necessary ingredient for both their development and progress, especially for individuals with ASD who show deficits in this area. Social interactions and relationships that emphasize understanding, involvement, and engagement between individuals are driven by motivations. Special Education and Training can achieve the aforementioned objectives by utilizing ICT and a variety of instructional methodologies. The inclusion of students with disabilities in regular classes is encouraged by modern pedagogy. a public, open-door school. New technologies are a tool that helps in this goal by changing conventional training into instruction for everyone. Consistent training that considers the unique traits, abilities, passions, and experiences of each student supports the creation and implementation of differentiated teaching, enabling all students to learn at their own pace and on their schedule. The scenario of personalized instruction in a health education program is presented in this essay.